Iodide Adsorption onto Three Organic–Inorganic Composite Adsorbents - Huifang Zhang; Tan Guo; Quan Li; Haining Liu; Xiushen Ye; Zhijian Wu (Adsorption Science & Technology)
Composite adsorbents, Ca(ALG) 2 –Cu 2 O, Ca(ALG) 2 –AgCl and Ca(ALG) 2 –Ag, were prepared using Cu 2 O, AgCl and Ag as the adsorption-active components and calcium alginate as the matrix material. The adsorption of iodide from aqueous solutions onto these adsorbents was investigated as a function of initial solution pH, temperature and co-existing NaCl. The loading of the adsorption-active components in the composite adsorbents is much higher than that in the reported composite adsorbents. In neutral solutions, the equilibrium adsorption amount follows the order of Ca(ALG) 2 –AgCl <> Ca(ALG) 2 –Ag >> Ca(ALG) 2 –Cu 2 O. The adsorption by Ca(ALG) 2 –AgCl is insensitive to pH, while the adsorption by Ca(ALG) 2 –Cu 2 O and Ca(ALG) 2 –Ag is pH dependent. The effect of temperature on the adsorption is more pronounced for Ca(ALG) 2 –Cu 2 O than for Ca(ALG) 2 –AgCl and Ca(ALG) 2 –Ag. The co-existing NaCl does not affect the adsorption by Ca(ALG) 2 –AgCl very much; however, it suppresses the adsorption by Ca(ALG) 2 –Ag, and especially, Ca(ALG) 2 –Cu 2 O. Chemical adsorption is the main mechanism for all the three adsorbents. Ca(ALG) 2 –AgCl was found to be the best adsorbent owing to its highest adsorption capacity, suitable adsorption rate and insensitivity to solution pH, temperature and co-existing NaCl.